The Linguistic Landscape of the Indian Himalayas - Saxena, Anju (Brill, 2023)
This monograph is a contribution to the documentation of the linguistic situation of the Kinnaur district in Himachal Pradesh (Indian Himalayas) which has been so far almost undescribed. The Sino-Tibetan languages Kinnauri and Navakat and the Indo-Aryan language Kinnauri Pahari, all spoken in Kinnaur, are described both individually and as parts of a multifaceted linguistic ecology that extends into the surrounding wider Himalayan region. The author combines traditional linguistic description and a quantitative computational procedure to disentangle genealogical and areal characteristics of the languages of Kinnaur.